Corner of the living room with wicker chair, and doors to other rooms - White, Angela Mary (1978)
Photo faisant partie d'une série associée à une dissertation trimestrielle d'étudiant(e) en folklore à l'université Memorial: « Description of a house in Port-au-Port East ». -- Photo is one of a series associated with a Memorial University folklore student term paper: "Description of a house in Port-au-Port East.